Innovations and recent trends in Shape Memory Alloy: a review - S. Kawate, Saurabh.; K N, Chethan.; G Keni, Laxmikant; Pai, Anand; N H, Padmaraj (International Journal of Engineering and Technology, 2018)
Smart materials are materials, which have a definite response to stimulus provided through a change in pressure, temperature and termed as shape memory alloys (SMA). In this review, the general concept of SMAâ€™s has been discussed along with shape memory effects. Shape memory material properties depend on phase shifting phenomena, which consist of pseudoelasticity and thermoelasticity. The basic SMA such as Ni-Ti (Nickel-Titanium) alloys, Copper (Cu) based SMA, Iron (Fe) based SMA are commonly used in the industry, Ni-Ti alloys are expensive but it has good super elasticity and superior mechanical properties. Cu and Fe based are economical as compared to the Ni-Ti alloys. The various fabrication techniques and common composition of the alloys have been discussed with in detail. Â